Intertextual Reading of Tolerance In The Narrative of The Prophet Solomon Through The Quran’s Cosmic Structure - Shofiatun Nikmah; Siti Rif’atus Sa’adah; Wardatul Jannah; Dewi Alhaa; Muhammad Hidayat; Khoiriyah Shofiyah Tanjung (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2026)
Discourse on tolerance in Islamic studies has thus far tended to be anthropocentric, limited to interfaith relations, and has paid insufficient attention to the cosmic dimension that also shapes religious ethics. There is a significant research gap regarding how Islamic texts address cosmic and ecological dimensions, leaving a conceptual void in applying religious ethics to the global environmental crisis. This article aims to reinterpret the story of Prophet Solomon in the Qur’an as a foundation for cross-cosmic tolerance that involves the relationships between humans, non-humans, and the structure of the universe. This study employs a qualitative approach using Izzat Darwazah’s tartīb nuzūlī method to understand the context of revelation, as well as Ferdinand de Saussure’s semiotic analysis to uncover the sign structure (signifier–signified) in the story of Prophet Solomon, particularly in Surah Ṣ ād and Surah al-Naml. Through sign analysis, the study identified three main findings: 1) Prophet Solomon’s relationship with the ants establishes an ethical model that advocates for vulnerable/marginalized entities and acknowledges their right to ecological sustainability. 2) His interaction with the hoopoe demonstrates just leadership that rejects absolute domination and prioritizes epistemic tolerance grounded in rational accountability. 3) Prophet Solomon’s relationships with the ants, the hoopoe, the jinn, the wind, and the Queen of Sheba represent a model of tolerance not based on domination, but rather on the recognition of the agency, rationality, and dignity of every cosmic entity. This story affirms that tolerance in the Qur’an is not merely a passive attitude toward difference, but an active strategy grounded in knowledge, symbols, and transformative spiritual experience. The tartib nuzūlī approach demonstrates a narrative shift from refuting political arrogance (mid-Makkiyah) toward a science-based cosmic diplomatic strategy (late-Makkiyah). The story of Prophet Solomon offers an active and holistic ecosentric ethical paradigm, relevant for addressing contemporary humanitarian and ecological crises